Pengaruh Harga, Ketepatan Waktu Pengiriman dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Jasa Pengiriman J&T Express Cabang Tanon Kabupaten Sragen - Khurrohman , Taufik; Junaidi , M Rofiq (Journal of Economics and Business Research (JUEBIR), 2023)
The aim of this research is to determine the effect of price, on time delivery and service quality on customer satisfaction at the J&T Express delivery service, Tanon Branch, Sragen Regency. The population of this research is the community in Tanon District. The sampling technique uses a probability sampling method with a random probability sampling technique. The research sample was 100 respondents. The research method used is a quantitative method and the data analysis used is multiple linear regression analysis. The results of this research show that price has a positive and significant influence on customer satisfaction with a calculated t value greater than t table, namely 2.830 > 1.6608 and has a significant value smaller than 0.05, namely 0.006, on time delivery has a positive influence and is significant for customer satisfaction with a calculated t value greater than t table, namely 3.507 > 1.6608 and has a significant value smaller than 0.05, namely 0.001, service quality has a positive and significant influence on customer satisfaction with a calculated t value of more larger than the t table, namely 4.797 > 1.6608 and has a significant value smaller than 0.05, namely 0.000.